2012
DOI: 10.1517/17425247.2012.668523
|View full text |Cite
|
Sign up to set email alerts
|

Exploring oral nanoemulsions for bioavailability enhancement of poorly water-soluble drugs

Abstract: Low-energy emulsification techniques can also produce stable nanoemulsions. It is guaranteed that oral nanoemulsions can act as a potential tool for the delivery of poorly water-soluble therapeutic moieties in a very efficient manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(72 citation statements)
references
References 62 publications
0
64
0
8
Order By: Relevance
“…27 Similarly, the active components encapsulated within NE droplets can be protected from oxidation, hydrolysis, and volatilization. 28 High-and low-energy approaches constitute the two major methods for formulating NE. 29,30 In industry, the formulation of NE is performed using the high-energy approach, which utilizes mechanical devices capable of generating intense disruptive forces that break up the oil and water phases, leading to the formation of tiny oil droplets.…”
Section: Introductionmentioning
confidence: 99%
“…27 Similarly, the active components encapsulated within NE droplets can be protected from oxidation, hydrolysis, and volatilization. 28 High-and low-energy approaches constitute the two major methods for formulating NE. 29,30 In industry, the formulation of NE is performed using the high-energy approach, which utilizes mechanical devices capable of generating intense disruptive forces that break up the oil and water phases, leading to the formation of tiny oil droplets.…”
Section: Introductionmentioning
confidence: 99%
“…28 Though these theories represent completely different flow regimes and were developed for macroemulsions, many modern nanoemulsion studies have referred to Taylor's theory as well as Hinze's theory to explain trends observed in droplet size. 2,17,18,20,23,[29][30][31][32][33][34][35][36][37] However, few studies also acknowledge that the agreement with Taylor's and Hinze's theory is only qualitative at best and that these theories should be used only for an order of magnitude estimation of droplet size. 17,23 Further, there are also experimental studies on nanoemulsion which do not use any theoretical prediction and fit their droplet size data using empirical power law correlations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as far as the method for improving solubility is concerned, molecular inclusion complexation technology might be equally or more effective and much simpler and easier for production scale-up than other approaches, such as emulsification and phospholipid complexation. 25,26 Formation of RAABCD was confirmed by differential scanning calorimetry and FTIR spectroscopy. As shown in Figure 3A, the differential scanning calorimetry thermogram for rifaldazine showed a sharp peak at 259°C, corresponding to the melting point of rifaldazine.…”
Section: Preparation and Characterization Of Raabcdmentioning
confidence: 93%